Impact of reduced human papillomavirus vaccination coverage rates due to COVID-19 in the United States: A model based analysis. Issue 20 (12th May 2021) - Daniels, Vincent; Saxena, Kunal; Roberts, Craig; Kothari, Smita; Corman, Shelby; Yao, Lixia; Niccolai, Linda
Abstract: The coronavirus disease 2019 (COVID-19) pandemic has significantly affected utilization of preventative health care, including vaccines. We aimed to assess HPV vaccination rates during the pandemic, and conduct a simulation model-based analysis to estimate the impact of current coverage and future pandemic recovery scenarios on disease outcomes. The model population included females and males of all ages in the US. The model compares pre-COVID vaccine uptake to 3 reduced coverage scenarios with varying recovery speed. Vaccine coverage was obtained from Truven Marketscan™. Substantially reduced coverage between March-August 2020 was observed compared to 2018–2019. The model predicted that 130, 853 to 213, 926 additional cases of genital warts; 22, 503 to 48, 157 cases of CIN1; 48, 682 to 110, 192 cases of CIN2/3; and 2, 882 to 6, 487 cases of cervical cancer will occur over the next 100 years, compared to status quo. Providers should plan efforts to recover HPV vaccination and minimize potential long-term consequences.